2013
DOI: 10.1063/1.4809640
|View full text |Cite
|
Sign up to set email alerts
|

In-situ atomic force microscopy study of the mechanism of surface relief grating formation in photosensitive polymer films

Abstract: When photosensitive azobenzene-containing polymer films are irradiated with light interference patterns, topographic variations in the film develop that follow the local distribution of the electric field vector. The exact correspondence of e.g., the vector orientation in relation to the presence of local topographic minima or maxima is in general difficult to determine. Here, we report on a systematic procedure how this can be accomplished. For this, we devise a new set-up combining an atomic force microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 40 publications
5
86
0
Order By: Relevance
“…[1][2][3][4] Azobenzene derivatives have been used as photoalignment molecules for liquid crystals [5][6][7][8] , optical memories [9][10][11][12][13][14][15] and when embedded in polymers for recording of polarization and surface relief gratings. [16][17][18][19][20][21][22] The reason of their exceptionally wide usage was linked with the molecular configurational trans-to-cis transition leading to the several opto-mechanical effects. [23][24][25][26] When azobenzene derivatives are attached to the polymer main chains they exhibit the Weigert effect 27 which describes the light induced molecular orientation of the transstate azobenzene molecules with their long molecular axes set perpendicularly to the plane of linearly polarized light incident on the polymer film.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Azobenzene derivatives have been used as photoalignment molecules for liquid crystals [5][6][7][8] , optical memories [9][10][11][12][13][14][15] and when embedded in polymers for recording of polarization and surface relief gratings. [16][17][18][19][20][21][22] The reason of their exceptionally wide usage was linked with the molecular configurational trans-to-cis transition leading to the several opto-mechanical effects. [23][24][25][26] When azobenzene derivatives are attached to the polymer main chains they exhibit the Weigert effect 27 which describes the light induced molecular orientation of the transstate azobenzene molecules with their long molecular axes set perpendicularly to the plane of linearly polarized light incident on the polymer film.…”
Section: Introductionmentioning
confidence: 99%
“…In order to follow the kinetic of the SRG inscription in-situ, a home-made set up combining optical part for generation of interference pattern and an AFM was applied. 26,27,35 The The experimental details of the Raman microscope and measurements of polymer surface relief gratings have been described elsewhere. 28 Here we describe in details experimental conditions related to the multilayer-graphene flakes (ML-graphene).…”
Section: Methodsmentioning
confidence: 99%
“…optical data storage, light processing, photomechanics and photofluidics stimulates development of novel materials and tools for material modifications. Photochromic materials, such as azo-functionalized polymers have been widely investigated [1][2][3][4][5] because of their unique features to undergo inducement of optical anisotropy and surface mass transport upon suitable laser light irradiation [6][7][8][9][10][11]. Recently it has been demonstrated that the chiral symmetry of light (angular momentum of photons in the beam) can be mapped via mass transport and surface pattern formation in azo-polymers [11].…”
Section: Introductionmentioning
confidence: 99%